Narn i chi'n hu'rin the tale of Children of hurin - Tolkien, J.R.R (John Ronald Reuel) 1892-1973 (Harper Collins, 2008)
A fantasy adventure saga set in the early days of Middle-Earth features humans and elves, dwarves and dragons, orcs and dark sorcerers clashing in an epic battle between good and evil